Influenza: Toward understanding the immune response in the young - Sakleshpur, Sonia; Steed, Ashley L. (Frontiers in Pediatrics, 2022)
Annually influenza causes a global epidemic resulting in 290,000 to 650,000 deaths and extracts a massive toll on healthcare and the economy. Infants and children are more susceptible to infection and have more severe symptoms than adults likely mitigated by differences in their innate and adaptive immune responses. While it is unclear the exact mechanisms with which the young combat influenza, it is increasingly understood that their immune responses differ from adults. Specifically, underproduction of IFN‐γ and IL-12 by the innate immune system likely hampers viral clearance while upregulation of IL-6 may create excessive damaging inflammation. The infant’s adaptive immune system preferentially utilizes the Th-2 response that has been tied to γδ T cells and their production of IL-17, which may be less advantageous than the adult Th-1 response for antiviral immunity. This differential immune response of the young is considered to serve as a unique evolutionary adaptation such that the young preferentially respond to infection broadly rather than a pathogen-specific one generated by adults. This unique function of the young immune system is temporally, and possibly mechanistically, tied to the microbiota, as they both develop in coordination early in life. Additional research into the relationship between the developing microbiota and the immune system is needed to develop therapies effective at combating influenza in the youngest and most vulnerable of our population.